Craniofacial growth changes foll.owing surgically created defect on title temporal mandibular joint - Hamid, Suzin'a Sheikh Ab (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Early craniofacial development patlnvay will generally affect the final general appearance of the face at the end of facial gro\vth period. The gro\vth of the face is a complex process involving many growth processes particularly in mandible, mid face and cranial base. These processes occur at the same time and the overall pattern of growth results ftom the interplay between them. They must all hannonized \\lith each other if a normal facial pattern is to result and a stnaU deviations from harmonious or interruption of the gro\vth at any point will affect the development of other grov..1h po-ints thus Iesulti:ng in dysmorphology of the craniofacial complex. Several studies have been carried out to determine the pattern, physics and kinetics. of gro~rth to. assist in further understanding of craniofacial de:ve.topment for eventual use. in c.raniofacial corrective surgery. Due to the small and infrequent number of craniofacial dysmoiphology cases in human as well as the difficulty and ethics issues involved when studying human models, most of the studies were carried out using animal models vherehy defects c.ould he c,o.nveniently induc.ed for research purpose and the result may be. extrapolated to the human facial growth. Mandibular growth depends largely on normal development of the tempo.romandihular joint (TMJ) and any disturbance. in its normal development Vill affect the growth in the dimension of the mandible 1. Due to interrelations in the various growth ih points, dysmorphology in the mandible will consequently create changes in the general developtnent of the craniofacial complex.